The preference of PE goats on poly-herb supplementation - Suteky, T.; Dwatmadji; Sutrisno, E. (International Journal of Agricultural Technology, 2022)
Our findings showed that there were no significant differences in sniffing and eating frequency also DMI. There is also an interaction amongst sniffing, eating frequency, pellets and DMI with the equation Y= 10.67- (0.405 Sniffing frequency) + (2.338 Eating frequency) -(0.706 pellet) +e, with the R2 = 0.506. However, when preconditioning/pre-ingestive goats with specific polyherbal pellets were calculated. Group of goats that previously eat pellets 0 the Dry matter intake (41.62 g/30 minutes) RPI, selection index and CoP were significantly higher (<0.05) than the others. Three pellets (P0. P1, P2) were high acceptable by PE goat while P3 was medium acceptable. The result from Mann-Whitney Wilcoxon-Test indicates that frequency of eating, DMI (g/30 min), selection index and RPI were significantly higher in preconditioning goats